Eficácia, efetividade e segurança do tratamento de oxigenoterapia através das câmaras hiperbáricas, para o tratamento de pacientes com queimaduras térmicas: uma síntese de evidência - Araújo, Luiza Dayane Santos (2025)
INTRODUCTION: Burns represent a significant cause of morbidity and mortality, with considerable impact on Brazilian public health. According to the Ministry of Health, it is estimated that approximately 1 million burn cases occur annually in Brazil, with around 100,000 patients requiring hospitalization and approximately 2,500 evolving to death. In this context, hyperbaric oxygen therapy (HBOT) emerges as a potential intervention to improve the healing of thermal burns. OBJECTIVE: To evaluate the efficacy and safety of hyperbaric oxygen therapy in the treatment of patients with thermal burns. MATERIAL AND METHODS: This is a synthesis of evidence from the literature. Primary studies (Randomized and Non-Randomized Clinical Trials, Case-Control Studies, Cohort Studies) and secondary studies (systematic reviews) investigating the effects of HBOT in patients with thermal burns were reviewed. The search was conducted in databases such as MEDLINE (via PubMed), BVS, EMBASE, clinical trial registries, and gray literature. Article selection occurred in two phases: independent screening by two reviewers of titles and abstracts, followed by full-text reading of eligible studies and risk of bias assessment using appropriate tools (Robins I and AMSTAR). Any disagreements in the process were resolved by a third reviewer. RESULTS: Hyperbaric oxygen therapy shows potential as an adjuvant therapy in the treatment of thermal burns, with observed benefits in wound healing, reduced need for grafts, and shorter hospital stays. In addition, its positive effects on inflammatory processes and angiogenesis reinforce its therapeutic value. However, the scarcity of robust randomized clinical trials limits the widespread adoption of HBOT. CONCLUSION: Therefore, future multicenter and methodologically rigorous studies are essential to confirm its efficacy, standardize protocols, and define precise indications, promoting safe and evidence-based use.